The 'functional matrix' hypothesis - current concepts and conflicts - Fuller David; West Victor (Sciendo, 1986)
The 'functional matrix' hypothesis and alternative hypothesis for the control of craniofacial growth are described. The functional matrix hypothesis has been seen as a useful means of accounting for observed growth phenomena. It is to be noted that, for some, there are important barriers to its universal application and acceptance. These barriers are highlighted in a presentation of evidence which supports or challenges the functional matrix hypothesis. An attempt is made to outline how the interpretation of this evidence is conflicting, and that given our present knowledge, the functional matrix hypothesis cannot be proved or disproved.